Enterococcus faecalis Promotes Innate Immune Suppression and Polymicrobial Catheter-Associated Urinary Tract Infection - Tien, Brenda Yin Qi (2017)
Enterococcus faecalis, a member of the human gastrointestinal microbiota, is an opportunistic pathogen associated with hospital-acquired wound, bloodstream, and urinary tract infections. E. faecalis can subvert or evade immune-mediated clearance, although the mechanisms are poorly understood. In this study, we examined E. faecalis-mediated subversion of macrophage activation. We observed that E. faecalis actively prevents NF-κB signaling in mouse RAW264.7 macrophages in the presence of Toll-like receptor agonists and during polymicrobial infection with Escherichia coli. E. faecalis and E. coli coinfection in a mouse model of catheter-associated urinary tract infection (CAUTI) resulted in a suppressed macrophage transcriptional response in the bladder compared to that with E. coli infection alone. Finally, we demonstrated that coinoculation of E. faecalis with a commensal strain of E. coli into catheterized bladders significantly augmented E. coli CAUTI. Taken together, these results support the hypothesis that E. faecalis suppression of NF-κB-driven responses in macrophages promotes polymicrobial CAUTI pathogenesis, especially during coinfection with less virulent or commensal E. coli strains.